“Cruel Fiends of Hell”: Slaughter at Sand Creek in the Name of Manifest Destiny - Swain, Christopher (Kansas State University. Dept. of History, 2012)
Throughout the study of American History, the story of the United States is seen in a relatively positive light through the rebellion against the oppressive British, freeing of the slaves to the unsympathetic Confederate slaveholders, and saving the world from Germanic tyranny in both world wars. However, little is known within the affairs of the nation regarding white settlers and the fate of the Native American. In American cinema, Indians are seen as the savage, cruel, and interfering race that hinders and scares the “white-man” into defending their family and community from impending attack. In contrast to this belief, upon further investigation through multiple primary documents such as newspaper articles, journal entries, and territorial and federal government documents, it appears that in actuality, the roles are switched. The ruthless white settlers impeded on the nomadic lifestyle of the Natives, creating hostile intentions, which led to the slaughter of thousands. In the instance of the Sand Creek Massacre, the conclusion has been drawn that the Native Americans were the victims as white territorial leadership such as Governor Evans, Colonel Chivington, and Major Anthony possessed Manifest Ideology ideals, which led to the horrendous actions. This study is to present a fair light on American history in regard to the Indian plight against their white counterpart. Due to the evidence, the underlining hatreds and objectives of the expanding Americans were not only surprising but also disturbing.
Keywords: Native Americans; Sand Creek Massacre; Manifest Ideology; Cheyenne Indians; Arapaho Indians